Assessment of bio-mulches on weed control in sunflower (Helianthus annuus L.): Assessment of bio-mulches on weed control in sunflower (Helianthus annuus L.) - B S VIDYASHREE; P MURALI ARTHANARI (Journal of Oilseeds Research, 2020)
A field experiment was conducted at Tamil Nadu Agricultural University, Coimbatore to evaluate bio-mulching to control weeds in sunflower during rabi, 2018-19. The experiment was carried out in RBD with three replications. The treatments comprised of Terminalia chebula powder @ 400 kg/ha, mango leaves @ 4 t/ha, tamarind leaves @ 4 t/ha, eucalyptus leaves @ 7 t/ha, mustard seed powder @ 160 kg/ha, neem leaves @ 2.5 t/ha, hand weeding at 30 and 45 DAS and un-weeded/unmulched. The results revealed that application of eucalyptus leaves mulch on the soil surface between the rows @ 7 t/ha was effective in controlling weeds and recorded lowest weed index (4.3) and produced seed yield of 2297 kg/ha which was on par with that of best treatment of hand weeding twice (2400 kg/ha). Crop yields were negatively correlated with weed index.